PERSEPSI DAN PARTISIPASI MASYARAKAT DUKUH MENANGGAL SURABAYA DALAM PILKADA LANGSUNG DI KOTA SURABAYA - A. Qomaru Zaman (Universitas PGRI Adi Buana, 2013)
This research reveals a problem of perception and participation of Dukuh Menanggal Surabaya citizen in the direct election of regional heads in Surabaya in 2010. The research objective was to assess the perceptions and participation of citizens in the form of views and forms of citizen action and community leaders both formal and non-formal education, in the face of direct election implementation in Surabaya. In addition, to assess the relationship between perception and participation of residents with social, economic and cultural This type of research includes descriptive qualitative research. Because the focus of research has been determined in advance, then the strategy of this research includes case studies spikes (embedded case study research). The data in this study is largely qualitative data extracted from the resource persons is 40 people, and from the archives/documents such as journals, newspapers and magazines. The selection of resource persons (sampling) using purposive sampling or criterion-based selection. The data were collected by in-depth interview techniques (depth Interviewing) and recorded documents (content analysis). To obtain accurate data the validity of the data used technique known as triangulation. While the data analysis with interactive analysis techniques From the data analysis it can be concluded: 1. Perception of Dukuh Menanggal Surabaya citizens against direct election in Surabaya. Generally they are positive/good or agree. However, there are some who see negatively or less agree, and even doubt/donÃ‚â€™t use the right to vote the direct election of Surabaya. 2. These are some of forms of direct citizen participation in Election, among others: the very high participation in election and determination of voters list on election participation is low, while participation at direct elections included in the category of less participation (low participation). 3. Perception and participation of Dukuh Menanggal Surabaya citizen in the election in Surabaya is very closely linked to the social, economic and cultural development. Both those who agree or are opposed and are hesitant to the direct general election have backgrounds in different social, economic or cultural.